PROBLEMS OF FORMATION OF THE ENVIRONMENT FOR THE DEVELOPMENT OF BARRIER-FREE TOURISM - Galina Shelkoplyasova; Tatyana Savenko (Вестник Северо-Кавказского федерального университета)
The article examines the dynamic growth of tourism contributing to the emergence of new species, areas and forms of organization of tourist service. In this regard, the theme of interaction ofpersons with disabilities in the tourism sector is very critical. The emergence of the new perspective directions of tourism in Russia -barrier-free tourism (tourism for people with disabilities) and the creation of conditions for availability of the tourist services to all categories of consumers is a priority in the system of strategic purposes of development of tourism in the country.